Anti-sticking isolation sand as well as preparation method and application thereof
By using cement and powdered inorganic materials to granulate high-round anti-adhesive isolation sand, the problems of inconsistent physical and chemical properties, energy consumption and secondary pollution of anti-adhesive isolation sand in the prior art are solved, and efficient Production process of improving bond strength and environmental protection and energy-saving.
Patent Information
- Application Number
- CN202411566718.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
AI Technical Summary
The existing anti-adhesive isolation sand has inconsistent physical and chemical properties due to the increase in configuration layer. The crushing process makes the particles sharp and not round, energy-consuming and secondary pollution problems.
Cement and powdered inorganic materials are used as the main raw materials to produce anti-adhesive isolation sand with high roundness and uniform particle size distribution through granulation equipment to avoid sintering and crushing processes, and achieve an environmentally friendly and energy-saving production process.
The bonding strength between the reverse sticking isolation sand and the post-cast concrete has been improved, and the peeling strength can be increased by up to 218%. The preparation method is stable and reliable, the production process is environmentally friendly and energy-saving, and the construction waste and industrial waste can be recycled and reused.
Smart Images

Figure CN119409465A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials, and in particular relates to anti-sticking isolation sand and a preparation method and application thereof. Background Art
[0002] In the construction of building projects, underground waterproofing projects mostly use the reverse-adhesive construction method with pre-laid self-adhesive membranes. The pre-laid reverse-adhesive construction method is to pre-lay the waterproof material on the base plate cushion layer, and then pour the structural concrete on the waterproof material. The upper surface of the waterproof material forms a reverse-adhesive bond with the concrete, and then the waterproof layer and the structural layer are bonded into one. In order to form a firm reverse-adhesive structure between the waterproof membrane and the structural concrete, an adhesive is generally applied to the upper surface of the waterproof membrane, or the waterproof material itself has a self-adhesive property, and then solid mineral particles are sprinkled on the adhesive layer or the self-adhesive material. The industry usually refers to this type of mineral particles as reverse-adhesive isolation sand, which has two functions: one is to enhance the adhesion between the waterproof membrane and the post-cast concrete, and the other is to prevent the waterproof membrane from sticking to itself during the winding and packaging process and to the on-site materials and operators during the construction process (a single material that prevents adhesion is also called an isolation material). The particle size of the reverse-adhesive isolation sand is usually less than 5mm. Commonly used isolation sands include natural sand, machine-made sand, sintered sand, and reactive sand. Natural sand is rock particles formed by natural conditions, such as river sand; machine-made sand usually refers to particles made of rocks and mine tailings through mechanical crushing and screening, with a rough appearance and sharp edges, such as crushed quartz sand; sintered sand is a particle made of minerals through high-temperature sintering and crushing, such as mullite sand; reactive sand, as the name suggests, usually refers to mineral particles that have certain reactive properties by adding additional compounds or treating their outer surfaces with chemical coupling agents. In addition to natural sand, other artificial sands such as machine-made sand, sintered sand, and reactive sand all require a crushing process, resulting in high production energy consumption. More importantly, the crushing process makes the particles irregular in shape, affecting the adhesion with the post-cast concrete; and its sharp edges are easy to damage the main waterproof material layer; the crushing process will generate dust, which is easy to pollute the environment; during use, the mixed fine powder components will also cause secondary pollution and endanger human health.
[0003] At present, common isolation sand has poor anti-adhesion and uneven bonding in practical applications. Specifically, the anti-adhesion effect of isolation sand with post-cast concrete needs to be improved due to its irregular particle shape; the bonding degree between the randomly scattered isolation sand and the adhesive layer also needs to be improved. In this regard, researchers have made various explorations.
[0004] Some researchers have proposed to modify the surface of anti-stick particles in order to increase the adhesion with concrete and bonding layer. For example, patent document CN 116179008A proposes a method of modifying the surface of particles using metal compounds, which is intended to improve the dispersion performance of surface-modified particles, prevent adhesion and agglomeration between particles, improve the reflectivity of surface-modified particles, and avoid the problem of increased alkalinity of water bodies after particles on waterproof membranes come into contact with water. In this method, the surface-modified particles are composed of a variety of base particles and a coating formed by metal compounds and coatings attached to the base particles. The coating attached to the base particles uses a coating prepared by 10-15% emulsion. The physical and chemical properties of the inner and outer layer materials of this type of surface-modified particles are inconsistent.
[0005] Some researchers have also proposed to improve the particle configuration. For example, patent document CN 112832392 A discloses a composite isolation sand with a multi-layer coating structure, which includes a mineral particle carrier, a transition layer, a functional shell layer and a surface protective layer arranged in sequence from the inside to the outside, and the functional shell layer includes acrylic emulsion, silicate cement and titanium dioxide. The preparation scheme of this composite isolation sand is intended to solve the problems of poor adhesion between natural mineral particles and the bonding layer and post-cast concrete, poor isolation and protection effect on the bonding layer, and easy rolling of the main reinforcement layer. It uses styrene / acrylate copolymer emulsion as the surface protective layer, and the particle configuration belongs to a "soft-encased hard" structure, and the physical and chemical properties of the inner and outer layer materials are inconsistent; the preparation process requires multiple drying processes such as 300°C, 700°C, and 500°C. This technical solution can appropriately smooth the sharp protrusions of the edges and corners of the mineral particles, but it cannot fundamentally change the external contour of the mineral particles themselves.
[0006] Patent document CN 114920482 A discloses a reactive cement white sand, which uniformly wraps liquid and powder on aggregates by layering, and quickly forms an outer protective layer of 0.1 to 0.15 mm through the reaction of cement and water. Its main body is cement-based, which can improve the affinity with cement paste in the later bonding process with post-cast concrete, thereby improving the adhesion and peeling strength. The A component of the reactive white sand, that is, the core layer aggregate, is a mixture of natural sand and artificial sand, which is an inorganic material. The B component and the C component use water-based latex and latex powder as binders, respectively, which are high molecular polymers. Their function is to bond and wrap the A component with materials such as heavy calcium powder and cement. This three-layer sandwich structure has inconsistent physical and chemical properties of the inner, middle and outer layer materials; the preparation process requires one and two aging.
[0007] Some researchers have proposed to strengthen the bonding between concrete and coiled materials by the migration of active ingredients. For example, patent document CN 116813282A discloses a reaction sand, the raw materials of which are 20-30 parts of ordinary Portland cement or white cement, 5-10 parts of silica fume, 0.1-0.3 parts of triethanolamine, 0.5-1.0 parts of nano-silicon dioxide, 40-60 parts of quartz powder, 0.3-0.6 parts of silane coupling agent, 0.2-0.3 parts of carboxylic acid water reducer, and 20-30 parts of water. The preparation method is to stir and mix the above raw materials into a viscous slurry, then absorb water under closed negative pressure, cure at room temperature for 6-8 days, and then crush to obtain 30-50 mesh modified reaction sand. Since this method requires a crushing process, the appearance and morphology of the obtained particles are similar to those of common artificial sand making.
[0008] Patent document application number 201080063366.3 discloses a waterproof membrane, on which the adhesive layer of the waterproof membrane is sprinkled with reflective inorganic particles, the average diameter of the inorganic particles is 100μm-600μm, which is approximately equal to or greater than the average thickness of the pressure-sensitive adhesive layer. Among them, the reflective particles made by hydrating and grinding the white cement for more than 7 days can also add one or more additives such as admixtures, antioxidants, UV stabilizers, and white pigments mixed therewith, water-based emulsions, etc. to the cement mixture to achieve the benefits of enhancing the bonding strength between new and old concrete and protecting the pressure-sensitive adhesive from degradation. The patent document intends to emphasize the reflection of white particles to light, and to achieve the covering protection of the adhesive layer by covering about 70%-100% of the exposed surface of the pressure-sensitive adhesive. In this scheme, the white cement needs hydration and curing for 7 days or more, and the subsequent process needs to crush, grind and screen the cement, which takes a long time, and the appearance of the resulting particles is similar to that of common artificial sand.
[0009] From the above, it can be seen that the current means of improving the anti-sticking performance of researchers are mainly to modify the surface coating materials of the isolation sand, adjust the internal components, and reduce the aging of the adhesive layer by increasing the coverage rate. These existing technologies, surface coating material modification, involve different configuration levels, and the added organic polymers will lead to inconsistent physical and chemical properties of the inner and outer layers of the particles and unstable configuration; the solution of adjusting the internal components by adding compounds has a complex preparation process, which is energy-consuming and time-consuming. The outer contour of the isolation sand prepared by the required crushing process is no different from that of common artificial sand making, and there is also the problem of secondary processing dust pollution during the crushing process, which does not meet the current requirements of high quality, low pollution, and sustainable development. Summary of the invention
[0010] In view of the problems that the current isolation sand has inconsistent physical and chemical properties due to the increase in configuration levels, the crushing process makes the anti-adhesive isolation sand sharp and not round, and it is energy-consuming and time-consuming to cause secondary pollution, the present invention provides anti-adhesive isolation sand and its preparation method and application, using cement and powdered inorganic materials as the main raw materials, through granulation equipment, to manufacture anti-adhesive isolation sand with high roundness and uniform particle size distribution, and use the anti-adhesive isolation sand to manufacture waterproof materials for pre-paving anti-adhesive waterproofing projects. A series of combined verification tests show that the anti-adhesive isolation sand prepared by the present invention has a good effect on improving the bonding strength between the anti-adhesive isolation sand and the post-cast concrete. Depending on the main material and the type of adhesive, the peeling strength can be increased by up to 218%; the preparation method is stable and reliable, no drying and crushing process is required in the production process, it is environmentally friendly and energy-saving, and can effectively realize the recycling and reuse of construction waste and various industrial waste residues.
[0011] The present invention is achieved through the following technical solutions:
[0012] The first aspect of the present invention provides an anti-adhesive isolation sand for building materials. The anti-adhesive isolation sand is a cement-based material. The anti-adhesive isolation sand is spherical or ellipsoidal, and its circularity is 0.79-1.0.
[0013] Furthermore, the circularity of the anti-sticky isolation sand is 0.83-0.99, and further 0.85-0.95.
[0014] It should be noted that there are many parameters that characterize the shape and morphology of particles, and different industries have different understandings and explanations of this. "Presentation of particle size analysis results Part 6: Qualitative and quantitative description of particle shape and morphology" (GB / T15445.6-2014) uses circularity (C) as a mesoscopic descriptor. Its calculation formula is:
[0015]
[0016] The present invention refers to GB / T 15445.6-2014 and combines the common practices in the industry to use roundness (R) as the particle characteristic. The calculation formula is:
[0017]
[0018] In the formula, A represents the area of the two-dimensional image projected by the particle, and P represents the perimeter of the two-dimensional image projected by the particle.
[0019] According to this formula, it can be easily deduced that, typically, the circularity of a perfect circle is 1.00, the circularity of a regular hexagon is 0.907, the circularity of a cube is 0.785, the circularity of a rectangle with an aspect ratio of 2:1 is 0.698, and the circularity of an equilateral triangle is 0.605. Obviously, the circularity R represents the degree to which the shape of a graphic is close to a circle. When R is 1, the graphic is a circle; the smaller R is, the more irregular the graphic is, and the greater the difference from the circle. For particulate matter, it essentially reflects the relative sharpness of the edges and corners of the particles. The more and sharper the edges and corners of the particles, the worse the circularity; conversely, the smoother the edges and corners, the better the circularity.
[0020] The measurement method is based on the current digital image processing (DIP) technology for measurement and statistics. The specific process is basically: taking pictures to obtain particle images, image binarization, particle contour extraction, parameter calculation (and data analysis).
[0021] The high circularity anti-sticky isolation sand of the present invention is spherical or ellipsoidal, and is characterized by the average circularity, that is, the circularity interval of the anti-sticky isolation sand is between 0.79 and 1.0; at the same time, it is also characterized by the ratio of the number of particles that meet the circularity requirements to the total number of particles. As long as more than 60% (including this number) of the anti-sticky isolation sand has a circularity of ≥0.80, it means that the circularity of the anti-sticky isolation sand meets the requirements.
[0022] Furthermore, the particle size of the anti-sticking isolation sand is 0.1-4.75 mm, further 0.15-2.5 mm, further 0.2-2.0 mm, and further 0.30-0.60 mm.
[0023] Furthermore, the coefficient of variation (CV) of the particle size of the anti-sticky isolation sand is ≤0.25.
[0024] The second aspect of the present invention provides a method for preparing the anti-sticking isolation sand: cement is used as a gelling material, powdered inorganic material is used as a filler, water is used as a binder, and auxiliary materials such as admixtures are also used, and granulation is performed through a granulating device to obtain spherical or ellipsoidal particles, which are screened according to particle size specifications and sealed and packaged to obtain the anti-sticking isolation sand of the present invention; further, the granulating equipment has a rotating function, and the powder is agglomerated into balls by rotation or rolling to achieve high-efficiency and low-energy granulation, and further, such as drum granulation, disc granulation, round pot granulation, cylinder granulation, high-speed and strong mixing granulation equipment.
[0025] Furthermore, in the solid raw materials, cement accounts for 5-100wt%, and powdered inorganic filler accounts for 0-95wt%; further, cement accounts for 20-60wt%, and powdered inorganic filler accounts for 40-80wt%; the binder is water; water accounts for 10-60% of the cement material, and further, 15-50%.
[0026] Furthermore, the cement is a compound of one or more of special cement and ordinary cement.
[0027] Further, the special cement is cement and its clinker and derivatives with special properties, special functions and special uses, and has the special property of rapid hardening; further, the special cement includes but is not limited to at least one of aluminate cement, sulphoaluminate cement, fluoroaluminate cement, ferroaluminate cement, aluminate cement clinker and its derivatives, sulphoaluminate cement clinker and its derivatives, ferroaluminate cement clinker and its derivatives, fluoroaluminate cement clinker and its derivatives, phosphate cement, phosphate cementitious material and its derivatives; further, preferably at least one of aluminate cement, sulphoaluminate cement, fluoroaluminate cement and ferroaluminate cement;
[0028] The ordinary cement is cement with silicate cement clinker as the main component, including but not limited to general silicate cement, white silicate cement, medium-heat silicate cement, low-heat silicate cement, sulfate-resistant silicate cement, oil well cement, road silicate cement, slow-setting silicate cement for road base, marine engineering silicate cement, silicate cement for nuclear power engineering, low-heat slag silicate cement, low-heat micro-expansive cement, calcium sulfoaluminate modified silicate cement, low-heat steel slag silicate cement, masonry cement, silicate cement clinker and at least one of its derivatives.
[0029] The derivatives referred to above are cement-based materials made with cement or its corresponding cement clinker as the main component and other functional auxiliary materials added, such as cement-based grouting materials prepared with fillers such as silicate cement, quartz sand, and admixtures such as water reducers and defoamers; for example, ordinary (O) type oil well cement made by grinding silicate cement clinker with hydraulic calcium silicate as the main component and adding an appropriate amount of gypsum that meets GB / T5483.
[0030] Furthermore, it is a binary compound of 0wt%-100wt% sulphoaluminate cement and 0wt%-100wt% general purpose Portland cement; further, it is a binary compound of 20wt%-70wt% sulphoaluminate cement and 30wt%-80wt% general purpose Portland cement.
[0031] Furthermore, the cement is one of P·O 42.5 ordinary silicate cement and P·C 42.5 composite silicate cement, or a mixture of the two; the rapid hardening cement is one of rapid hardening sulphoaluminate cement R·SAC 42.5 and aluminate cement CA50, or a mixture of the two.
[0032] Furthermore, the powdered inorganic filler includes but is not limited to at least one of fine concrete powder, brick powder and fly ash, kiln ash, limestone powder, slag powder, phosphorus slag powder, steel slag powder, carbide slag, metal tailings powder, quartz sand powder, river sand powder, gypsum, desulfurized gypsum, red mud, silica ash, volcanic ash and blast furnace slag inorganic materials in the process of recycling construction waste.
[0033] Furthermore, the particle size of the powdered inorganic filler is 0.01-1.0 mm, and further, 0.05-0.2 mm.
[0034] Furthermore, at least one of an admixture, an adhesion promoter, and a pigment is used, and the amount used is calculated based on the total amount of cement material in the solid raw material. The amount of the admixture is 0.1wt%-7wt%, the amount of the adhesion promoter is 0.001wt%-6.0wt%; and the amount of the pigment is 0.1wt%-16wt%.
[0035] Furthermore, the admixture includes but is not limited to a water reducer; further, it is a polycarboxylic acid water reducer, and further, it is a granular polycarboxylic acid water reducer with a water reduction rate of about 20%.
[0036] Furthermore, the adhesion promoter is an organic or inorganic adhesion promoter, or a combination of the two; further, a safe and non-toxic organic microbial-based polysaccharide is used as the adhesion promoter; further, xanthan gum is used; further, an inorganic adhesion promoter is also used; further, layered silicate clay minerals are used; further, attapulgite powder is used.
[0037] The pigment adopts alkali-resistant pigment, and further, alkali-resistant mineral pigment is selected; further, stable inorganic pigments such as iron oxide red, iron oxide yellow, iron oxide black, titanium dioxide and their composite application are adopted.
[0038] The third aspect of the present invention provides the application of anti-adhesive isolation sand in the production of pre-laid and self-adhesive waterproof materials and the pre-laid anti-adhesive method. In the production of pre-laid and self-adhesive waterproof materials, the anti-adhesive isolation sand of the present invention is spread on the upper surface of the waterproof roll material to achieve a smoother and cleaner production effect; in the construction of the pre-laid anti-adhesive method, a better anti-adhesive bonding effect can be achieved, and the peeling strength between the waterproof material and the post-cast concrete can be stably improved.
[0039] The waterproof material can be rubber, plastic, rubber-plastic composite polymer sheet material, asphalt-based coiled material, or a waterproof material composited from at least two different types of materials.
[0040] The present invention has the following beneficial effects:
[0041] 1. The anti-adhesive isolation sand prepared by the present invention can maximize the contact interface with the adhesive layer of the waterproof coiled material, thereby maximizing the bonding strength.
[0042] The inventors of this application found in the research process that the circularity of the existing isolation sand in the industry is generally below 0.78, and the lowest circularity is even lower than 0.50, which leads to poor adhesion with the adhesive layer or the main self-adhesive material. The inventors also found through further research that isolation sand with low circularity has poor fluidity, and it is not easy to spread evenly and form effective coverage during the factory production and covering process. In addition, its sharp shape has many edges and corners, which can easily damage the flexible waterproof membrane body. During the construction process, people walking, activities stepping on, and heavy pressure of steel bars and materials will further aggravate the damage to the main body of the material. The anti-adhesive isolation sand of the present invention has a high degree of roundness and a regular external morphology, and thus: (1) the sand mold is spherical / ellipsoidal, has good fluidity, does not require more power to lower the sand during sand covering, and has low production energy consumption; (2) when used in the production of sand covering, it can be conveniently controlled to achieve uniform spreading, thus avoiding the phenomenon of insufficient and unbalanced adhesion of irregular sand to the adhesive layer during sand covering; (3) its overall morphology is regular and controllable, and the surface of the waterproof material is uniform after sand covering, which is conducive to the stress release of the material after production and winding and packaging; (4) the sand-covered surface of the waterproof material prepared by it is flat, which has the least effect on the fluidity of the post-cast concrete, and can make the post-cast concrete fully dense during the vibration process, ensuring a good increase in the hydration degree and strength of the post-cast concrete at the interface joint. (5) Its regular external morphology can produce controllable and regular gaps between particles, so that the cement slurry in the later poured concrete can be deeply poured into the gaps between particles, achieving complete bonding and further improving the bonding strength; (6) After being spread on the waterproof material, it produces controllable and balanced fine particle gaps, which can effectively block coarse and fine aggregates such as sand and gravel in the concrete, thereby protecting the flexible waterproof membrane body from the impact damage of sharp aggregates during the concrete pouring and vibration process.
[0043] 2. Compared with artificial sand manufacturing processes such as natural ore crushing and sintering crushing, the anti-sticking isolation sand of the present invention does not require sintering or crushing during the production and preparation process, and has low comprehensive energy consumption, which is beneficial to energy conservation and helps to reduce environmental pollution such as waste and dust; comprehensive utilization of waste such as fly ash, slag, and industrial mine tailings powder as fillers is beneficial to the environmentally friendly reuse of waste resources; the particle size range of the manufactured anti-sticking isolation sand is controllable and has good uniformity; compared with common cement particles, it does not require 5-7 days or longer maturation and no further crushing; the product has good roundness and no sharp protrusions; during engineering construction, there is no need to worry about damage caused by subsequent operations such as steel bar bundling, material handling, temporary storage, and other links.
[0044] 3. The anti-sticking isolation sand of the present invention adopts a one-time molding production method. The materials are fully mixed during the preparation process, and the finished product is spherical / ellipsoidal particles after molding. There is no hard-soft, soft-hard or hard-soft-hard hierarchical configuration, and the overall performance is uniform and stable;
[0045] 4. The anti-sticking isolation sand of the present invention uses cement and various sand powders and other inorganic powders as main raw materials, which are all general inorganic materials for construction. Its own composition and admixtures are similar to the concrete configuration used in construction projects, and are of the same material as the post-poured concrete, with almost the same physical and chemical properties, good compatibility, and its durability and reliability have been fully verified and recognized. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a comparison diagram of the appearance of the anti-sticking isolation sand prepared in Example 1 and the common isolation sand on the market;
[0047] Figure 2 The outline diagram of the isolation sand and the crushing process reaction sand prepared in Example 1 after being photographed and binarized;
[0048] Figure 3 This is a normal distribution diagram of the circularity data of the isolation sand and the commercially available reaction sand in Example 2;
[0049] Figure 4 A ranking chart of the percentage of circularity of the anti-sticking isolation sand produced by the present invention and the commercially available reaction sand;
[0050] Figure 5 This is a cross-sectional measurement diagram of the finished waterproof material made of the isolation sand of the present invention and the isolation sand available on the market;
[0051] Figure 6 This is a comparison diagram of the peeling interface between the waterproof membrane prepared by the isolation sand of the present invention and the commercially available isolation sand and the post-cast concrete. DETAILED DESCRIPTION
[0052] The present invention is further described in detail below with reference to specific embodiments and accompanying drawings.
[0053] If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels. The particle size unit is millimeter, and its comparison with the mesh number is based on industry practice and refers to the American Taylor sieve system.
[0054] 1. Preparation of anti-sticking isolation sand
[0055] Example 1
[0056] The invention discloses a method for preparing the present invention, comprising the following steps: comprising: a cement material of 40 wt %; a powdered inorganic filler of 60 wt %; an admixture of 2.1 wt % of the total amount of cement materials in the raw materials; and a bio-based adhesion promoter of 0.11 wt % of the cement materials in the raw materials; and a pigment iron red of 5 wt % of the cement materials in the raw materials; wherein the cement is a binary compound of 50 wt % sulphoaluminate cement R﹒ SAC 42.5 and 50 wt % ordinary Portland cement P﹒ O 42.5; the powdered inorganic filler is 0.05-0.15 mm (100-325) mesh fine river sand; the admixture is a polycarboxylic acid-based water reducer; and the bio-based adhesion promoter is xanthan gum.
[0057] The cement, powdered inorganic filler and pigment are fully mixed in advance; the admixture and adhesion promoter are dissolved in water according to the proportion to form a mixed solution. The mixed solution is added to the mixed material by atomization spraying using a rotary drum granulation device, and the total amount of the mixed solution is controlled to be 23% of the cement material. Screening is performed according to the specification requirements to obtain particles of the required particle size, and the particles are sealed and packaged to obtain the anti-sticking isolation sand of the present invention. Figure 1 The figure on the right shows the macroscopic morphology of the anti-sticking isolation sand of the present invention.
[0058] Example 2
[0059] Cement 80wt%, powdered inorganic filler 20wt%, admixture is 1.13wt% of cement material in raw materials, bio-based adhesion promoter is 0.018wt% of cement material in raw materials, pigment iron red is 2wt% of cement material in raw materials; wherein, cement is 100wt% sulphoaluminate cement R﹒ SAC 42.5; powdered inorganic filler is silica fume SF90, and its specific surface area is 22000㎡ / kg; admixture is polycarboxylic acid water reducer, and bio-based adhesion promoter is xanthan gum. Granulate according to the preparation process of Example 1, wherein the total amount of mixed solution is 22.5% of cement material. Screen according to specification requirements to obtain particles of required particle size, seal and package, and obtain the anti-sticking isolation sand of the present invention.
[0060] Example 3
[0061] Cement 50wt%, powdered inorganic filler 50wt%, admixture is 0.5wt% of cement material in the raw material, bio-based adhesion promoter is 0.074wt% of cement material in the raw material, pigment is 0wt% of cement material in the raw material; wherein, cement is a binary compound of 15wt% sulphoaluminate cement R﹒ SAC 42.5 and 85wt% composite silicate cement P﹒ C 42.5; powdered inorganic filler is fine powder with a particle size less than 0.15mm (100 mesh sieve residue) in the process of recycling concrete recycled aggregate, admixture is polycarboxylic acid water reducer, and bio-based adhesion promoter is xanthan gum. Granulation is carried out according to the preparation process of Example 1, wherein the total amount of the mixed solution is 46% of the cement material. Screening is carried out according to the specification requirements to obtain particles of the required particle size, and sealed packaging is obtained to obtain the anti-sticking isolation sand of the present invention.
[0062] Example 4
[0063] The cement is 100wt%, the powdered inorganic filler is 0wt%, the admixture is 0.3wt% of the cement material in the raw material, the bio-based adhesion promoter is 0.021wt% of the cement material in the raw material, and the pigment iron red is 5.0wt% of the cement material in the raw material; wherein, the cement is a binary compound of 15wt% sulphoaluminate cement R﹒ SAC 42.5 and 85wt% composite silicate cement P﹒ C 42.5; the admixture is a polycarboxylic acid-based water reducer, and the bio-based adhesion promoter is xanthan gum.
[0064] Add the above-mentioned cement, powdered inorganic filler and pigment into a strong mixing granulator and mix them thoroughly in advance; dissolve the above-mentioned additives and adhesion promoters in water according to the proportion to form a mixed solution. Add the mixed solution into the granulation container according to the proportion of 20.5% of the cement material, mix at high speed, and then stir and granulate at low speed. Screen according to the specification requirements to obtain particles of the required particle size, seal and package, and the anti-sticking isolation sand of the present invention is obtained.
[0065] Example 5
[0066] The cement is 100wt%, the powdered inorganic filler is 0wt%, the inorganic adhesion promoter is 2.1wt% of the cement material in the raw material, and the pigment is 2wt% of the cement material in the raw material; wherein the cement is a binary compound of 20wt% aluminate cement CA50 and 80wt% white silicate cement P·W-242.5, the pigment is titanium dioxide, and the inorganic adhesion promoter is attapulgite powder.
[0067] Dissolve the adhesion promoter in water at a ratio of 9%, stir and mix for 1 hour to form a mixed slurry. Add the cement and pigment into a strong mixing granulator and mix them thoroughly in advance; add the mixed slurry into a granulation container at a ratio of 23% of the cement material, mix at high speed, and then stir and granulate at low speed. Screen according to the specification requirements to obtain the isolation sand of the required particle size, which is the high circularity anti-adhesive isolation sand of the present invention.
[0068] The high circularity anti-sticking isolation sand in Examples 1-5 was sieved according to the specification of 0.2-1.0 mm (16 mesh-80 mesh), and its circularity was measured and compared with the circularity of reaction sand and sintering sand of common specifications in the industry. The comparison results are shown in Table 1:
[0069] Table 1 Circularity of Example Isolation Sand and Common Isolation Sand
[0070]
[0071] 2. Roundness of anti-sticking isolation sand
[0072] Figure 1 The following are photos of three types of isolation sand commonly used in the industry and the isolation sand of the present invention. It can be seen that the isolation sand of the present invention is a relatively regular sphere or ellipsoid, with a more rounded shape, no edges or corners on the surface, and a relatively uniform particle size; while the existing isolation sand is irregular in shape, with many and sharp edges and corners on the surface, rarely rounded in shape, and with uneven particle sizes. The isolation sand of the present invention and the commonly used reaction sand in the commercial industry with a particle size range of 0.2-1.0 mm were randomly selected, and the images were captured by a digital camera. The outline of the binarized shape is shown in the figure below. Figure 2 shown.
[0073] The same number of particles of the anti-sticking isolation sand prepared in Example 2 and the common reaction sand on the market were randomly selected, and microscopic digital photos were taken. Then, the digital image processing (DIP) technology was used to perform roundness detection and statistics. The specific values of the roundness of the two sands are shown in Table 2, and the further data analysis results are shown in Table 3. The normal distribution of the roundness R value is shown in Table 3. Figure 3 .
[0074] It can be seen that the mean circularity of the anti-sticky isolation sand prepared in Example 2 of the present invention is 0.875, and the mean circularity of the artificial (crushed) reactive isolation sand is 0.778; the proportion of the circularity of the anti-sticky isolation sand of the present invention ≥ 0.79 is 98.3%, while the proportion of the circularity of the reactive isolation sand ≥ 0.79 is only 45.9%; the circularity of the anti-sticky isolation sand of the present invention is as low as 0.778 and as high as 0.931, and the circularity of the reactive isolation sand is as low as 0.610 and as high as 0.872; the standard deviation of the circularity data of the anti-sticky isolation sand of the present invention is 0.0299, and the standard deviation of the reactive sand is 0.0509; Figure 3 It shows that the circularity measurement values of the anti-sticky isolation sand of the present invention and the artificial (crushed) reaction type isolation sand are in line with the normal distribution, and the peak of the anti-sticky isolation sand of the present invention is higher than that of the artificial (crushed) reaction type isolation sand, that is, the anti-sticky isolation sand of the present invention has the characteristics of high circularity and narrow distribution. The circularity and distribution of the isolation sand of the present invention are significantly better than those of the existing isolation sand.
[0075] Table 2 Roundness and standard deviation of the anti-sticking isolation sand and the crushing process isolation sand of the present invention
[0076]
[0077]
[0078] Table 3 Roundness interval distribution of the anti-sticking isolation sand prepared by the present invention and the commercially available reaction sand
[0079]
[0080]
[0081] Generally, when the number of samples is greater than 30, the data are approximately in accordance with the normal distribution. For the typical characteristics of a large number of fine particles, the normal distribution characteristics are even more consistent. The data in Tables 1 and 2 show that the proportion of the anti-adhesive isolation sand of the present invention with R≥0.79 is 98.3%, while the proportion of the commercially available reaction sand with R≥0.79 is only 45.0%. The above measurement data are ranked by percentage, see Figure 4 .
[0082] The inventor has conducted a large number of measurements and data analysis on various other isolation sands available on the market, and based on the above data analysis and distribution table, combined with Figure 4 The percentage ranking chart confirms that as long as more than 60% (including this number) of the anti-sticking isolation sand particles have a circularity ≥ 0.80, it can be shown that the circularity of the anti-sticking isolation sand generally meets the requirement that its average value is not less than 0.79.
[0083] Therefore, in view of the stability and reliability of the preparation method of the present invention, the proportion of the roundness R ≥ 0.80 of the anti-sticky isolation sand is not less than 60% of the total number as a distinguishing feature of the preparation method of the anti-sticky isolation sand of the present invention and other isolation sand preparation methods.
[0084] 3. Particle size distribution of anti-sticky isolation sand
[0085] The anti-sticky isolation sand prepared in Examples 1-5 of the present invention and the commercial isolation sand were selected for particle size measurement, and descriptive statistics were performed on the data, and further analysis and data processing were performed. The relevant data are shown in Table 4. Data analysis shows that the CV mean of the anti-sticky isolation sand prepared by the method of the present invention is 0.184, and the CV mean of the isolation sand prepared by the crushing process is 0.297. It can be seen that the anti-sticky isolation sand prepared by the method of the present invention and the common commercial isolation sand prepared by the crushing process have obvious differences in coefficient of variation (CV).
[0086] After extensive particle size measurement and data analysis of the anti-sticky isolation sand of the present invention and other isolation sands that require a crushing process, and taking into account actual engineering needs, the inventor sets the threshold value of the coefficient of variation CV to 0.25. That is, CV≤0.25 indicates that the anti-sticky isolation sand meets the particle size distribution requirements and can significantly improve its bonding performance with post-cast concrete.
[0087] Table 4 Descriptive statistical comparison of particle size of the anti-sticking isolation sand of the present invention and commercial isolation sand
[0088]
[0089]
[0090] 4. Preparation of pre-laid waterproof materials using anti-adhesive isolation sand and its anti-adhesive effect
[0091] 1. Waterproof material prepared by isolation sand of the present invention and its distribution on waterproof membrane
[0092] The anti-adhesive isolation sand prepared by the present invention and commercially available isolation sand are spread to make waterproof materials, and relevant bonding performance experiments are carried out.
[0093] Specifically, according to the different substrates, there are two methods for preparing pre-laid and self-adhesive waterproof materials:
[0094] (1) Polymers. The polymer resin particles, inorganic fillers and additives are mixed evenly in a high-speed mixer, the materials are melted and extruded through a screw extruder, and cooled and shaped through a three-roll calender to obtain a sheet, which is the main material layer of the polymer waterproof material; the heated self-adhesive adhesive is applied to the main material layer, which is the self-adhesive film waterproof material; the isolation sand prepared in Example 2 is spread on the self-adhesive layer of the self-adhesive film waterproof material, and rolled to obtain a polymer pre-laid waterproof roll.
[0095] (2) Asphalt-based. Heat the asphalt, add the modifier, tackifier and inorganic filler in turn, stir and mix evenly, and develop to obtain a modified asphalt-based self-adhesive coating. The asphalt-based self-adhesive coating is applied to the polyester base cloth through an impregnation process. After primary cooling, the anti-adhesive isolation sand with a particle size of 0.3-0.85 mm (20-50 mesh) prepared and sieved in Example 1 is sprinkled on the asphalt surface of the asphalt-based self-adhesive waterproof material, and rolled to obtain an asphalt-based polyester base pre-laid waterproof membrane.
[0096] The anti-sticking isolation sand of the present invention and other types of isolation sand are spread on the coils of different materials as the main material layer, and the particle distribution of the cross-section side is shown in FIG. Figure 5 It can be seen that the particles of the isolation sand of the present invention are arranged regularly and orderly, and the overall material plane regularity after sand coating is better than that of the existing commonly used isolation sand.
[0097] 2. Peeling strength between the isolation sand waterproofing membrane of the present invention and the post-cast concrete
[0098] According to the test method of GB / T 23457-2017 "Pre-laid waterproof membrane", the peeling strength between the membrane and the post-cast concrete was tested, and microscopic observation and photography were taken to record the surface conditions of the concrete side of the peeling interface. For details, see Figure 6 . Figure 6 In the figure, the red circle shows the voids on the surface of the post-cast concrete. The number of voids on the peeling interface of the anti-adhesive isolation sand of the present invention is much smaller than that of other types of isolation sand.
[0099] Example 6
[0100] Main waterproof material: commercially available rubber EPDM polymer sheet, hot melt adhesive thickness 0.5 mm. Type of isolation sand: 0.25-0.85 mm (20-60 mesh) isolation sand sieved in Example 1 of the present invention, and Xiamen ISO standard sand, a legal reference material dedicated to the cement concrete industry.
[0101] The experimental results show that for this type of waterproof material, the peeling strength between the roll material coated with the isolation sand of the present invention and the post-cast concrete is higher than the peeling strength between the roll material coated with the ISO standard sand. The peeling strength between the isolation sand group of the present invention and the post-cast concrete is 55.1% higher than that of the standard sand group, which is significantly improved. The calculated value of the coefficient of variation CV of the data shows that the isolation sand of the present invention has better data stability, and its bonding effect with the post-cast concrete is higher and more stable. However, the numerical discreteness of using ISO standard sand as the sand-coating material is relatively large.
[0102] Table 5 Peeling strength and stability of sand-covered waterproof membrane and post-cast concrete
[0103]
[0104]
[0105] Example 7
[0106] Main material of waterproof material: plastic HDPE sheet, hot melt adhesive thickness 0.25 mm. Type of isolation sand: isolation sand prepared in Example 1 of the present invention, ISO standard sand.
[0107] The experimental results are shown in Table 6. For this waterproof material, the peeling strength between the coiled material covered with the isolation sand of the present invention and the post-cast concrete is significantly higher than that between the coiled material covered with ISO standard sand and the post-cast concrete, and the peeling strength improvement rate of the former reaches 218%. This shows that the roundness of the anti-adhesive isolation sand of the present invention has a significant effect on improving the peeling strength.
[0108] Table 6 Peel strength between sand-covered HDPE sheet and post-cast concrete
[0109]
[0110] Example 8
[0111] Main waterproof material: rubber-plastic TPR sheet, hot melt adhesive thickness 0.25 mm. Types of isolation sand: isolation sand in Example 2 of the present invention, commercially available reaction sand, quartz sand, blue quartz sand, and a non-covered sand group are set to compare the effects of different types of isolation sand on the peeling strength of post-cast concrete.
[0112] As shown in Table 7, for this type of waterproofing membrane, the isolation sand of the present invention has a good peeling strength enhancement effect compared to the material without sand coating, and its average peeling strength is 1.616N / mm. However, not all commercially available isolation sand groups have the effect of enhancing peeling strength, and some have a weakening effect, with an average peeling strength of 1.116N / mm. In terms of peeling strength, the isolation sand group of the present invention has an average peeling strength of 44.8% higher than that of the commercially available isolation sand group with post-cast concrete.
[0113] Table 7 Peel strength between uncoated / coated TPR sheet and post-cast concrete
[0114]
[0115]
[0116] Example 9
[0117] The isolation sand of the present invention prepared in Example 3 was compared with the fine powder in the process of recycling concrete recycled aggregate (hereinafter referred to as concrete fine sand). The rubber-based EPDM polymer material coated with a commercially available hot melt adhesive with a thickness of 0.30 mm was used as the substrate, and the isolation sand of the present invention and the concrete fine sand were respectively covered to detect and compare the peeling strength with the post-cast concrete. The results show that the isolation sand of the present invention with a spherical or ellipsoidal appearance and the concrete fine sand with a sharp angular appearance have a significant effect of improving the peeling strength with the post-cast concrete, with the highest improvement rate of 81.3% and the average improvement rate of 74.3%.
[0118] Table 8 Comparison of peeling strength between the isolation sand / concrete powder sand TPR sheet of the present invention and the post-cast concrete
[0119]
[0120] Example 10
[0121] The EPDM material with butyl rubber of 0.45 mm thickness was selected as the main material layer, and the commercially available reaction sand and the anti-adhesive isolation sand prepared in Example 1 and Example 4 were respectively covered, and the peeling strength of the concrete poured thereafter was tested and compared. The results show that the waterproof material prepared by the anti-adhesive isolation sand of the present invention has a significant effect of improving the peeling strength compared with the commercially available reaction sand. The highest improvement rate is 103.86%.
[0122] Table 9 Comparison of the peeling strength between the isolation sand / reaction sand coated with EPDM material and the post-cast concrete
[0123] serial number Peel strength with post-cast concrete (N / mm) Improvement rate Commercially available reaction sand group 1.536 not applicable Example 1 Isolation sand group 2.276 48.16% Example 4 Isolation sand group 3.132 103.86%
[0124] Embodiment 11
[0125] In this embodiment, the isolation sand of the present invention in Example 1 is used, and the particle size specification is similar to the commonly used specifications in the industry. The isolation sand of the present invention is spread on the butyl self-adhesive film waterproofing membrane, and the same type of pre-laid polymer self-adhesive waterproofing membrane (reaction sand) on the market is selected at the same time. With reference to the environment after the pre-laid reverse bonding method, the peeling strength of the butyl self-adhesive film waterproofing membrane using the isolation sand of the present invention and the post-cast concrete is tested over time. The results are shown in Table 10.
[0126] The experimental results show that as the hydration process of the post-cast concrete increases (to the usual 28-day standard age), the peel strength between the pre-laid self-adhesive waterproofing membrane covered with the anti-adhesive isolation sand of the present invention and the post-cast concrete will continue to increase, and the 28-day peel strength continues to increase by more than 30% over the 7-day measurement value specified in the product standard, while the growth rate of the reactive sand with the same particle size specification is only 8.5%. This shows that the anti-adhesive isolation sand of the present invention has a great effect on improving the bonding firmness between it and the adhesive layer.
[0127] Table 10 Peel strength of the isolation sand-butyl film waterproofing membrane of the present invention and the post-cast concrete over time Unit: N / mm
[0128]
[0129] Example 12
[0130] A commercially available polymer modified asphalt polyester pre-paved waterproofing membrane with a thickness of 4 mm was selected and covered with 0.3-0.85 mm (20-50 mesh) river sand and the same particle size anti-adhesive isolation sand prepared in Example 4, and the peeling strength with the post-cast concrete was tested and compared. The results show that the pre-paved waterproofing material prepared by the isolation sand of the present invention has a significant effect of improving the peeling strength with the post-cast concrete compared with the commercially available river sand, and the improvement rate is 49.4%.
[0131] Table 11 Comparison of peeling strength between the anti-adhesive isolation sand / yellow sand covered sand of the present invention and the post-cast concrete
[0132]
[0133] The embodiments described above are only descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should fall within the protection scope determined by the claims of the present invention.
Claims
1. An anti-sticking isolation sand, characterized in that: The anti-sticking isolation sand is a cement-based material, and the anti-sticking isolation sand is spherical or ellipsoidal, and its circularity is 0.79-1.
0.
2. The anti-sticking isolation sand according to claim 1, characterized in that: The circularity of the anti-sticking isolation sand is 0.83-0.
99.
3. The anti-sticking isolation sand according to claim 1, characterized in that: The circularity of more than 60% of the anti-sticky isolation sand is ≥0.
80.
4. The anti-sticking isolation sand according to claim 1, characterized in that: The particle size of the anti-sticking isolation sand is 0.1-4.75 mm.
5. The anti-sticking isolation sand according to claim 1, characterized in that: The particle size of the anti-sticking isolation sand is 0.20-2.0 mm.
6. The anti-sticking isolation sand according to claim 1, characterized in that: The coefficient of variation of the particle size of the anti-sticky isolation sand is ≤0.
25.
7. The method for preparing the anti-sticking isolation sand according to any one of claims 1 to 6, characterized in that: Cement is used as a gelling material, powdered inorganic material is used as a filler, and water is used as a binder; among the solid materials, cement accounts for 5-100wt%, and the inorganic filler accounts for 0-95wt%; water accounts for 10-60% of the cement material, and granulation is performed by a granulating device to obtain spherical or ellipsoidal particles, which are the anti-sticky isolation sand.
8. The preparation method according to claim 7, characterized in that: The granulating device has a rotating function and aggregates the powder into granules by rotating or rolling.
9. The preparation method according to claim 7, characterized in that: The cement is a compound of one or more of special cement and ordinary cement.
10. The preparation method according to claim 9, characterized in that: The special cement is a cement with fast-hardening properties, including but not limited to at least one of aluminate cement, sulphoaluminate cement, fluoroaluminate cement, ferroaluminate cement, and phosphate cement; the ordinary cement is a cement with silicate cement clinker as the main component, including but not limited to at least one of general silicate cement, white silicate cement, masonry cement, silicate cement clinker and its derivatives.
11. The preparation method according to claim 10, characterized in that: The cement is a mixture of one or more of 0wt%-100wt% of special cement with rapid hardening properties and 0wt%-100wt% of ordinary cement.
12. The preparation method according to claim 7, characterized in that: The inorganic filler includes but is not limited to fine concrete powder and brick powder obtained from the recycling process of construction waste, as well as at least one of fly ash, kiln dust, limestone powder, slag powder, phosphorus slag powder, steel slag powder, tailings powder, quartz sand powder, river sand powder, zeolite, red mud, silica ash, volcanic ash, gypsum, desulfurized gypsum, and blast furnace slag inorganic materials.
13. The preparation method according to claim 7, characterized in that: At least one of an admixture, an adhesion promoter and a pigment is also used; calculated based on the total amount of cement in the solid raw material, the amount of the admixture is 0.1wt%-7wt%, the amount of the adhesion promoter is 0.001wt%-6.0wt%; and the amount of the pigment is 0.1wt%-16wt%.
14. The preparation method according to claim 13, characterized in that: The admixture includes but is not limited to a water reducer, the adhesion promoter includes but is not limited to microbial polysaccharide or layered silicate clay mineral powder, and the pigment is an alkali-resistant pigment, including but not limited to an inorganic pigment.
15. Application of the anti-adhesive isolation sand according to any one of claims 1-6 and 8-14 in the manufacture of pre-laid self-adhesive waterproof materials and the construction of pre-laid anti-adhesive construction method, characterized in that: The anti-adhesive isolation sand is spread and covered on a waterproof material with an adhesive layer or with self-adhesive properties to achieve a full adhesion effect with the post-cast concrete and improve the peeling strength between the waterproof material and the post-cast concrete.
16. The use according to claim 15, characterized in that The waterproof material is a rubber-based polymer waterproof material, a plastic-based polymer waterproof material, a rubber-plastic composite polymer waterproof material, an asphalt-based waterproof material, or a waterproof material composited from at least two of the above materials.
Citation Information
Patent Citations
Waterproof membrane
CN102725139B
Composite isolation sand and preparation method thereof
CN112832392A
Preparation method of cement reaction type white sand
CN114920482A
Surface modified particles, waterproof coiled material and preparation method of waterproof coiled material
CN116179008A
Improved reaction sand and preparation method thereof
CN116813282A